Effects of Stocking Densities on Growth and Production Performance of Mystus cavasius in Bottom Clean Aquaculture System - Md. Rabiul Awal; A. K. M. Saiful Islam; Md. Moshiur Rahman; Asma Jaman; Md. Harunor Rashid; Anuradha Bhadra (Aquaculture, Fish and Fisheries)
ABSTRACT Optimizing the stocking density in bottom clean aquaculture is essential for promoting fish growth, economic sustainability and enhancing the general well‐being of fish. Three stocking densities (low, medium and high) were tested in a bottom clean aquaculture system to evaluate the growth efficiency, nutritional values, blood parameters, and cost‐effectiveness of Mystus cavasius. Fish stocking rates in tanks were 666 (low density), 1000 (medium density) and 1330 fish/m3 (high density) with an initial fish weight of 0.49 ± 0.19 g, 0.48 ± 0.18 g and 0.50 ± 0.20 g, respectively. The results suggested that the water quality assessment was within acceptable limits for fish growth. The study revealed significantly higher (p < 0.05) final weight, weight gain, percentage weight gain, average daily weight gain, specific growth rate, survival rate and feed conversion ratio (FCR) in the low‐density treatment. However, the total fish yield and profit were significantly higher in the high‐density treatment compared to the medium‐density and low‐density treatments, resulting in a higher net profit. Nutrient values were similar across all treatments. The length–weight relationship analysis indicated a negative allometric growth (b < 3) with no significant variation (p > 0.05) among treatments. The blood glucose and haemoglobin levels ranged from 129.50 to 157.75 mg/dL and 8.40 to 8.80 g/dL, respectively, among treatments indicating optimum levels. This study suggests that the ideal density for M. cavasius in tank‐based bottom clean aquaculture is 1330 fish/m3. However, further research is necessary to investigate higher stocking densities for optimal production.